Contextualizing and optimizing novel strategies to improve the latent TB continuum of care: Insights from people living with HIV and health care providers in Brazil. - Isadora Salles; Paula Travassos; Renata Spener-Gomes; Ana Paula Loch; Valeria Saraceni; Lilian Lauria; Solange Cavalcante; Jamile Garcia de Oliveira; Alexandra Brito de Souza; Allyson Guimarães Costa; Sumire Sakabe; Roberta Schiavon Nogueira; et al. (Public Library of Science (PLoS), 2023)
Tuberculosis (TB) causes 1 in 3 deaths among people living with HIV (PLHIV). Diagnosing and treating latent tuberculosis infection (LTBI) is critical to reducing TB incidence and mortality. Blood-based screening tests (e.g., QuantiFERON-TB Gold Plus (QFT+)) and shorter-course TB preventive therapy (TPT) regimens such as 3HP (3 months weekly isoniazid-rifapentine) hold significant promise to improve TB outcomes. We qualitatively explored barriers and solutions to optimizing QFT+ and 3HP among PLHIV in three cities in Brazil. We conducted 110 in-depth interviews with PLHIV, health care providers (HCP) and key informants (KI). Content analysis was conducted including the use of case summaries and comparison of themes across populations and contexts. LTBI screening and treatment practices were dependent on HCP's perceptions of whether they were critical to improving TB outcomes. Many HCP lacked a strong understanding of LTBI and perceived the current TPT regimen as complicated. HCP reported that LTBI screening and treatment were constrained by clinic staffing challenges. While PLHIV generally expressed willingness to consider any test or treatment that doctors recommended, they indicated HCP rarely discussed LTBI and TPT. TB testing and treatment requests were constrained by structural factors including financial and food insecurity, difficulties leaving work for appointments, stigma and family responsibilities. QFT+ and 3HP were viewed by all participants as tools that could significantly improve the LTBI cascade by avoiding complexities of TB skin tests and longer LTBI treatment courses. QFT+ and 3HP were perceived to have challenges, including the potential to increase workload on over-burdened health systems if not implemented alongside improved supply chains, staffing, and training, and follow-up initiatives. Multi-level interventions that increase understanding of the importance of LTBI and TPT among HCP, improve patient-provider communication, and streamline clinic-level operations related to QFT+ and 3HP are needed to optimize their impact among PLHIV and reduce TB mortality.